BIOINFORMATICS, BETWEEN NECESSITY AND CHALLENGES: AN INDONESIAN PERSPECTIVE - Kholis Abdurachim Audah (Lembaga Penelitian Universitas Trisakti, 2018)
Biological Information is a priceless asset for many purposes. FromIndonesian perspective, this become more important due to the fact thatIndonesia is one of the richest country in the world in terms of biodiversityboth in the ocean and on the land. In addition, Indonesia is also a country withfourth largest population in the world. All these natural resources can be verypowerful if they are well managed and optimally utilized. A large collection ofdata (Big Data) can be obtained from different levels of organization oforganisms. These data can then be processed, analysed and interpreted tobecome important biological information that eventually being utilized for thebetterment of mankind. In order to obtain such big data and turns the datainto a meaningful information, scientists require a set of tools such asBioinformatics. Bioinformatics is a interdisciplinary field of studies thatencompasses different area of sciences which includes Biological Sciences,Medical Sciences, Computer Sciences, Mathematics and Statistics. This opensup a wide range of collaborative works, from field to bench involving both“wet” and “dry” laboratory. In this article, the necessity of implementingbioinformatics and challenges are discussed from Indonesian point of view.